Majaz Isti’arah in Qur’an Surah Al-Baqarah: A Balaghah Science Perspective Based Analysis - Murdiono Murdiono; Muhamad Amin; Hadi Nur Taufiq (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2022)
PurposeThis study examined the Majaz Isti'arah contained in the Qurán Surah (Q.S) Al-Baqarah according to the Perspective of Balaghah Science. Majaz isti'arah wasa part of the majaz lughawi which discussed the use of a word that was not in its real sense.MethodThe study relied on verbal data in the form of Quranic verses taken from Q.S Al-Baqarah through carefully reading to identify Majaz isti'arah. The identified Majaz isti'arah were qualitatively in accordance with Balaghah science perspective. It was done by balaghah scholars to get the most appropriate interpretation.Results/FindingsThe study found out that in Q.S. Al-Baqarah has 19 verses of Majaz Isti'arah. They were distributed into Majaz Isti'arah tasrihiyah with nine verses, namely Q.S. Al-Baqarah (2): 7, 16, 41, 49, 138, 143, 168, 175, 187, and Isti'arah makniyah with nine verses, namely Q.S. Al-Baqarah (2): 9, 27, 74, 81, 93, 250, 256, 257, 259; Isti'arah thaba'iyyah there with 15 verses, namely In Q.S. AlBaqarah (2): 7, 16, 27, 41, 49, 74, 81, 93, 143, 168, 175, 187, 250, 257, 259; Isti'arah Tamstsiliyah, with two verses, namely, Q.S. Al-Baqarah (2): 138, 266; and Isti'arah ashliyah with two verses, namely Q.S. Al-Baqarah (2): 138, 256.ConclusionThe data illustrates the existence of the isti'arah majaz which cannot be separated in understanding the Qur'an in particular. Q.S. Al-Baqarah. Therefore, this study suggests the need to explore the science of balaghah and further research on other suras in the Qur'an.